Development of a Scoring-Based Renewable Energy Readiness Index for Commercial Buildings: An Integrated Framework Based on Energy Audit Findings - Andry Riyanto; Erkata Yandri (Leuser Journal of Environmental Studies, 2026)
The building sector plays a significant role in global energy consumption and carbon emissions, necessitating the integration of renewable energy systems. However, conventional energy audits primarily focus on technical efficiency and do not provide a structured assessment of a building’s readiness for renewable energy implementation. This study addresses this gap by developing a Renewable Energy Readiness Assessment Framework (RERAF) and its corresponding Renewable Energy Readiness Index (RERI), which integrate energy audit findings with multidimensional readiness factors. The framework comprises nine dimensions—technical, managerial, economic, regulatory, environmental, social, digital, resilience, and institutional—operationalized through an evidence-based scoring approach using a standardized Likert scale (0–4). To maintain methodological neutrality at the initial development stage, all dimensions and indicators are assigned equal weights (equal weighting scheme), thereby avoiding subjective bias in the absence of expert-based validation. The framework was applied to a commercial office building in Indonesia using energy audit data, supporting documents, and operational information. The results show a RERI score of 2.39 (equivalent to 60.00 on a normalized scale), indicating a moderate level of readiness. The analysis reveals a structural imbalance between relatively strong technical readiness and weaker non-technical dimensions, particularly in managerial, economic, digital, and institutional aspects. These findings highlight that technical feasibility alone is insufficient to ensure successful renewable energy adoption. The proposed framework contributes to bridging the gap between energy audit practices and renewable energy readiness assessment by providing a transparent, evidence-based, and reproducible decision-support tool for stakeholders in the building sector.